Anaplasma phagocytophilum in sheep and goats in central and southeastern China. Issue 1 (December 2016) - Yang, Jifei; Liu, Zhijie; Niu, Qingli; Liu, Junlong; Han, Rong; Guan, Guiquan; Li, Youquan; Liu, Guangyuan; Luo, Jianxun; Yin, Hong
Abstract Background Anaplasma phagocytophilum is wide spread throughout the world and impacts both human and animal health. Several distinct ecological clusters and ecotypes of the agent have been established on the basis of various genetic loci. However, information on the genetic variability ofA. phagocytophilum isolates in China represents a gap in knowledge. The objective of this study was to determine the prevalence and genetic characterization ofA. phagocytophilum in small ruminants in central and southeastern China. Methods The presence ofA. phagocytophilum was determined in 421 blood samples collected from small ruminants by PCR. Positive samples were genetically characterized based on 16S rRNA andgroEL genes. Statistical analyses were conducted to identify ecotypes ofA. phagocytophilum strains, to assess their host range and zoonotic potential. Results Out of 421 sampled small ruminants, 106 (25.2%) were positive forA. phagocytophilum . The positive rate was higher in sheep (35.1%, 40/114) than in goats (26.4%, 66/307) (P  < 0.05). Sequence analyses revealed that the isolates identified in this study were placed on two separate clades, indicating that two 16S rRNA variants ofA. phagocytophilum were circulating in small ruminants in China. However, analysis using obtainedgroEL sequences in this study formed one cluster, which was separate from other known ecotypes reported in Europe. In addition, a novelAnaplasma sp. was identified and closely related to an isolate previously reported inHyalomma asiaticum, which clustered independently from all recognizedAnaplasma species. Conclusions A molecular survey ofA. phagocytophilum was conducted in sheep and goats from ten provinces in central and southeastern China. Two 16S rRNA variants and a new ecotype ofA. phagocytophilum were identified in small ruminants in China. Moreover, a potential novelAnaplasma species was reported in goats. Our findings provide additional information on the complexity ofA. phagocytophilum in terms of genetic diversity in China.